TAṬWÎR KITĀB AL-QIRĀ’AT AL-RASYÎDAH LI TARQIYYAH MAHĀRAH AL-QIRĀ’AH ‘INDA AL-ṬĀLIBAH BI ISTIKHDĀM AL-KITĀB AL-ELEKTRÛNY AL-TAFĀ’ULIY FI AL-MADRASAH AL-MUTAWASSIṬAH INSĀN QUR’ĀNY ACEH BESAR - Muslim, Buhori; Zikrina, Zikrina; Mukhlisah, Mukhlisah (Universitas Islam Negeri Ar-Raniry, 2023)
Based on the research problem, which is the teaching of reading skills using the book